2013
DOI: 10.3390/toxins5081475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decreased Vitamin D and Accumulated Uremic Toxin on Human CYP3A4 Activity in Patients with End-Stage Renal Disease

Abstract: In patients with end-stage renal disease, not only renal clearance but also hepatic clearance is known to be impaired. For instance, the concentration of erythromycin, a substrate of cytochrome P450 3A4 (CYP3A4), has been reported to be elevated in patients with end-stage renal disease. The purpose of this study is to elucidate the reason for the decrease in hepatic clearance in patients with end-stage renal disease. Deproteinized pooled sera were used to assess the effects of low-molecular-weight uremic toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Studies of ESRD have shown that CMPF indirectly inhibits the activity of cytochrome P450 3A4 (CYP3A4). 31,32 An important drug-metabolizing enzyme, CYP3A4 activity is altered in patients afflicted with ESRD through its association with the VDR, with CYP3A4 expression being controlled by both VDR and the pregnane X receptor (PXR) which are induced by 1,25(OH)D. 31,34 In cases of ESRD, increases in uremic toxins of 10-fold or more 32 limit the ability of VDR to bind to vitamin D response elements and inhibit CYP3A4 activity. 31 CYP3A4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of ESRD have shown that CMPF indirectly inhibits the activity of cytochrome P450 3A4 (CYP3A4). 31,32 An important drug-metabolizing enzyme, CYP3A4 activity is altered in patients afflicted with ESRD through its association with the VDR, with CYP3A4 expression being controlled by both VDR and the pregnane X receptor (PXR) which are induced by 1,25(OH)D. 31,34 In cases of ESRD, increases in uremic toxins of 10-fold or more 32 limit the ability of VDR to bind to vitamin D response elements and inhibit CYP3A4 activity. 31 CYP3A4…”
Section: Discussionmentioning
confidence: 99%
“…A furan fatty acid metabolite, CMPF has been linked with numerous diseases, including type-2 diabetes (T2D), end-stage renal disease (ESRD) and gestational diabetes mellitus (GDM). [29][30][31] In its association with ESRD and chronic renal failure, CMPF is characterized as a uremic toxin 31,32 that is created when furan fatty acids are incorporated into phospholipids and cholesterol esters, catabolized and excreted in the urine 33 possibly altering renal vitamin D metabolism. Studies of ESRD have shown that CMPF indirectly inhibits the activity of cytochrome P450 3A4 (CYP3A4).…”
Section: Discussionmentioning
confidence: 99%
“…Hippuric acid, indoxyl sulfate, CMPF and p-cresol all individually inhibit CYP3A4 mediated metabolism of testosterone in human microsomes [47]. Additionally, a combination of hippuric acid, CMPF, indoxyl sulfate and indole-3-acetic acid also perpetrate a significant decrease of CYP3A4 mRNA expression [53]. Indoxyl sulfate also inhibits CYP3A4 activity in human hepatocytes and microsomes, animal models and potentially in kidney disease patients [5456].…”
Section: Phase I Metabolic Pathwaysmentioning
confidence: 99%
“…Indoxyl sulfate plasma concentrations are inversely related to CYP3A4 activity measured by endogenous 4β-hydroxycholesterol formation in stable renal transplant patients [57]. Conversely, some reports suggest that indoxyl sulfate or other microbial toxins have no interactions with CYP3A4 activity or expression [53,58]. The reason for discordant findings between studies is unclear, but might be due to differences in experimental procedures.…”
Section: Phase I Metabolic Pathwaysmentioning
confidence: 99%
“…Hepatic metabolic function has been more widely shown to be affected by individual uremic toxins. The commonly‐studied toxin, indoxyl sulfate, has been repeatedly shown to affect hepatic synthetic production and elements of drug metabolism . p‐Cresol has also been shown to affect drug metabolism within the liver, as well as influencing hepatic uptake of other toxic substances such as aluminium .…”
Section: The Uremic Toxin Burden In Dialysis Patientsmentioning
confidence: 99%